Biology and Ecology of Dog Conch (Strombus Canarium Linnaeus, 1758) (Gastropoda: Strombidae) From Merambong Shoal, Johor Straits, Malaysia - Che Cob, Zaidi (2008)
Strombus canarium Linnaeus, 1758, locally known as „siput gonggong‟ is a prosobranch gastropod from the family Strombidae that was highly associated with seagrass bed ecosystem. The main objectives of this study were to investigate and document the life history characteristics, biology, and ecology of the species, which are currently not well established. This study has been conducted at Merambong Shoal, Johor Straits, Malaysia. Sample collections were conducted using a belt transect method where all individuals within the transect area were collected. The population dynamic was analyzed using both the Electronic Length Frequency Analysis (ELEFAN) and Length-based Fish Stock Assessment (LFSA) approaches, incorporated in the FiSAT software package. Apart from field observation, field experimentation and laboratory analyses, laboratory culture experiment (from egg mass to juvenile) was also conducted, using a standard larval culture protocol. Strombus canarium produced a long gelatinous tube of egg strand in the form of an egg mass. It took between 4.5 to 5.5 days of incubation before hatching, and the planktotrophic larvae spent between 18 to 24 days in the planktonic stage before metamorphosed. Metamorphic cue associated with bio-active materials from sediment taken from its nursery habitat showed the strongest effects compared to sediment conditioned seawater, seagrass detritus, seagrass detritus leachate, Potassium Chloride (KCL) and -aminobutyric acid (GABA). Changes of behavioral patterns related to metamorphosis were described, which can be divided into 3 phases: initiation, actual metamorphosis, and completion, resulted in completely camouflaged juveniles. In their natural habitat, juveniles can be found at specific localities (nurseries), characterized by low to medium density Halophila bed; high sediment organic content; high sorting coefficient, and low mean grain size. The adult population was widely distributed, but present in local colonies, and was highly seasonal in abundance. Based on the gonadosomatic index (GSI), combined with other biological, ecological and behavioral observations, it could be concluded that the species was highly seasonal in reproduction, which starts from November to late March. The population showed sexual polymorphisms where 3 different sexual morphs present i.e., males, normal females, and imposex females. Imposex was characterized by superimposition of male sexual characters on female. The imposex females showed significantly larger and heavier shell, and higher degree of outer-lip flaring compared to males and normal females. Imposex severity was defined as Stage 0 without the male genital system; Stage 1 with the appearance of rudimentary penis, but without penis duct; Stage 2 with simple prong of penis and penis duct, but without accessory; and Stage 3 with male penis complete with accessories. Development of other male characters as outlined in the general scheme of imposex evolution in prosobranchs was never observed. The percentage incidence of imposex (%I) was lower compared to other gastropod within the study areas, and there was no case of female sterility observed. In population dynamic studies, a total of 766 males and 1322 females have been sampled from January to December 2005. Growth parameter estimation using both the ELEFAN-I and LFSA methods showed higher asymptotic length (L∞) value in females compared to the males, but there was no significant difference in growth constant (K) and age at zero-length (to) of both sexes. The mean growth rate during the first year growth was estimated at 2.66 ± 0.16 mm/month for male and 4.59 ± 0.59 mm/month for female, which was comparable with the actual growth recorded using mark-recapture technique. The growth performance index (φ‟) was slightly lower in male (φ‟=3.48) compared to the female (φ‟=3.81), but both was well within the values reported for other marine gastropods. Recruitment patterns, together with observations on spawning and copulation suggest that the species was highly synchronized (seasonal) in reproduction. The production and biomass was also seasonal, significantly higher during the wet monsoon season compared to the dry season. In conclusions, many aspects of life history, biology, and ecology of S. canarium had been established. However more studies are urgently needed for better understanding and better management of the species, and for advancement of the species into mariculture.